Understanding enablers and barriers in Indonesia’s noncommunicable disease program: A qualitative study from nurses’ perspectives - Yoyok Bekti Prasetyo; Shiena Wahyu Ramadan; Sri Sunaringsih Ika Wardojo; Yulis Setiya Dewi; Titih Huriah (International Journal of Noncommunicable Diseases)
Context: Ineffectively implemented community-based noncommunicable disease (NCD) programs can severely impact public health, often leading to a rise in chronic conditions such as diabetes and cardiovascular diseases. Aims: This study aims to fill this gap by exploring the insights and experiences of nurses through qualitative research, offering a deeper understanding of the factors influencing the effective delivery of NCD services in Indonesia. Materials and Methods: This qualitative research focuses on six nurses implementing NCD programs at community health centers. Data were collected through in-depth, semistructured interviews and analyzed using thematic analysis. Participants were selected through purposive sampling, targeting those with a minimum of two years of experience in NCD program implementation. Recruitment was facilitated through collaboration with local health departments, who assisted in identifying eligible nurses and inviting them to participate in the study. Results: Thematic analysis identified three key supporting factors: (1) cadre empowerment as a driving force, (2) cross-sectoral and village support as crucial resources, and (3) community engagement through collaboration. Conversely, three main challenges were identified: (1) resource constraints that hinder program execution, (2) timing conflicts affecting participant engagement, and (3) data entry bottlenecks that complicate monitoring and evaluation. Conclusion: The study concludes that while cadre empowerment, cross-sectoral support, and community involvement are vital for the program’s success, overcoming barriers such as resource limitations, engagement issues, and data management challenges is crucial for improving the program’s effectiveness and sustainability in managing NCDs at the community level.